MATHEMATICS AND MATHEMATICS EDUCATION FOR THE ENTIRE HUMAN RACE: A CHALLENGE FOR THE 21ST CENTURY - ABDULLAHI, HARISU; ABDULLAHI, ABDULLAHI AUWAL (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
This paper shows that Mathematics education is purely a human activity. Conceptualizing mathematics education as the activity of few isolated specialists to the detriment of the realm of human cultures makes it not attractive to many students and the human race in general. If mathematics is to become a common property of humanity,mathematicians themselves need to learn to transcend their own tribal inclinations to not only entertain the possibility that the observations and stories of people that are not mathematicians are relevant, but to begin actively valuing them to genuinely open the mathematics educators’ community to all people that want to study mathematics. Hence, our mathematics education curriculum should be redesigned to bear on broad concerns of all rather than to train mathematicians, but to engage all students with Mathematics, and develop supplementary specialized curricular for those aspiring for professional careers in Mathematics related fields.